Histiocytic and Dendritic Cell Sarcomas of Hematopoietic Origin Share Targetable Genomic Alterations Distinct from Follicular Dendritic Cell Sarcoma. (6th May 2021) - Massoth, Lucas R.; Hung, Yin P.; Ferry, Judith A.; Hasserjian, Robert P.; Nardi, Valentina; Nielsen, G. Petur; Sadigh, Sam; Venkataraman, Vinayak; Selig, Martin; Friedmann, Alison M.; Samore, Wesley; Killian, Jonathan Keith; et al.
Abstract: Background: Histiocytic and dendritic cell neoplasms are a diverse group of tumors arising from monocytic or dendritic cell lineage. Whereas the genomic features for Langerhans cell histiocytosis and Erdheim-Chester disease have been well described, other less common and often aggressive tumors in this broad category remain poorly characterized, and comparison studies across the World Health Organization diagnostic categories are lacking. Methods: Tumor samples from a total of 102 patient cases within four major subtypes of malignant histiocytic and dendritic cell neoplasms, including 44 follicular dendritic cell sarcomas (FDCSs), 41 histiocytic sarcomas (HSs), 7 interdigitating dendritic cell sarcomas (IDCSs), and 10 Langerhans cell sarcomas (LCSs), underwent hybridization capture with analysis of up to 406 cancer-related genes. Results: Among the entire cohort of 102 patients, CDKN2A mutations were most frequent across subtypes and made up 32% of cases, followed by TP53 mutations (22%). Mitogen-activated protein kinase (MAPK) pathway mutations were present and enriched among the malignant histiocytosis (M) group (HS, IDCS, and LCS) but absent in FDCS (72% vs. 0%; p < .0001). In contrast, NF-κB pathway mutations were frequent in FDCSs but rare in M group histiocytoses (61% vs. 12%; p < .0001). Tumor mutational burden was significantly higher in M group histiocytoses as compared with FDCSs (median 4.0/Mb vs. 2.4/Mb; p = .012). We also describe a pediatric patient with recurrent secondary histiocytic sarcoma treated with targeted therapy and interrogated by molecular analysis to identify mechanisms of therapeutic resistance. Conclusion: A total of 42 patient tumors (41%) harbored pathogenic mutations that were potentially targetable by approved and/or investigative therapies. Our findings highlight the potential value of molecular testing to enable precise tumor classification, identify candidate oncogenic drivers, and define personalized therapeutic options for patients with these aggressive tumors. Implications for Practice: This study presents comprehensive genomic profiling results on 102 patient cases within four major subtypes of malignant histiocytic and dendritic cell neoplasms, including 44 follicular dendritic cell sarcomas (FDCSs), 41 histiocytic sarcomas (HSs), 7 interdigitating dendritic cell sarcomas (IDCSs), and 10 Langerhans cell sarcomas (LCSs). MAPK pathway mutations were present and enriched among the malignant histiocytosis (M) group (HS, IDCS, and LCS) but absent in FDCSs. In contrast, NF-κB pathway mutations were frequent in FDCSs but rare in M group histiocytosis. A total of 42 patient tumors (41%) harbored pathogenic mutations that were potentially targetable by approved and/or investigative therapies. Abstract : Histiocytic and dendritic cell neoplasms are a diverse group of tumors arising from the monocytic or dendritic cell lineage. This article presents the molecular characteristics of the four major subtypes of malignant histiocytic and dendritic cell neoplasms, focusing on genomic alterations that could represent therapeutic targets.